Design of monolithic microwave integrated circuit filters using electromagnetic simulation / Ahmad Asari Sulaiman - Sulaiman, Ahmad Asari (2005)
This thesis reports a research carried out to design monolithic microwave integrated circuit (MMIC) low pass filters using circuit and electromagnetic simulations. The filters were designed to be constructed on both Si and GaAs semiconductor wafers. The principal objectives were to reduce both circuit size and spurious content. Three types of designs are proposed here. The first is a Butterworth filter made of commensurate stubs, while the second filter is of the m-derived type. Both filters are realized using a single gold layer on the semiconductor substrate. The stub filter exhibited filtering action with a cut-off frequency of 10 GHz. In the m-derived filter design, the metal and substrate layers used were optimized with the aid of the electromagnetic simulator to improve the steepness at the transition region. The filter demonstrated a maximally flat passband with a cut-off frequency of 10 GHz and passband and stopband insertion losses of 0.2 dB and greater than 20 dB respectively. The overall size of the circuit was 1.296 × 1.6 mm2, smaller than filters constructed from transmission lines designed by other workers. The filters used standard materials compatible with MMIC technology. The third filter uses a novel metal/polyimide/metal multilayer structure consisting of buried coplanar waveguide and polyimide overlay. Two via holes were used to connect the coplanar waveguide to a transmission line at the top. The structure and the materials used are compatible with MMIC processing. Owing to the unique multilayer architecture, the filter operates well without spurious in the passband and stopband. The combination of several different materials in the structure also reduces the size. The proposed filter has a cut-off frequency of 3 GHz and an area of 1.0 × 0.7 mm2 while the stopband insertion and return losses were 20 dB and 25 dB respectively. Optimum performance was obtained when the metal and polyimide thicknesses were 5 μm each. A theoretical model to explain the new structure and design methodology are discussed in detail. To the author’s knowledge this project constitutes the first local work on multilayer MMIC filter designed using electromagnetic simulation. Due to the fact that electromagnetic signals tend to radiate into space at microwave frequencies, more accurate designs were made possible using electromagnetic simulators in this work. I would like to thank my supervisor Associate Professor Dr. Zaiki Awang of Microwave Technology Centre (MTC), Universiti Teknologi MARA for his support and encouragement through out the duration of my study. This work would not have been possible without his guidance and input. I also would like to thank the Postgraduate Coordinator Associate Professor Dr. Hj. Mohd Asri Hj. Mansor and the Dean of the Faculty of Electrical Engineering for their advice and assistance during the completion of this work. My deepest and special thanks go to the Ministry Of Science, Technology and Innovation (MOSTI) for the financial support. I would also like to thank all my colleagues at the faculty and the staff of Microwave Technology Centre who have assisted in numerous ways. Finally I would like to express my sincere appreciation to my parents and my family, especially to my wife and the children, for their support and encouragement during the study.